Edukasi Kesehatan Mental Emosial pada Anak Remaja - Asrina Pitayanti; Kartika Kartika; Fitria Yuliana (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The development of adolescence is a period of achieving mental, emotional, social, physical maturity, which is also a transition period from childhood to adulthood. This condition certainly requires adaptation in adolescents, 40% of adolescents admit to feeling more easily offended or angry, but 36% of them feel anxious or nervous. Another 36% feel tired or exhausted during class and 31% show feelings of stress. The purpose of implementing this community service activity is to teach adolescents about emotional mental health, so that adolescents can avoid the dangers caused by trying to prevent the incidence of mental disorders in adolescents. This community service activity was carried out in the youth group by providing education. The activity was attended by 28 adolescents. The activity was carried out well. Based on the results of the evaluation carried out using a questionnaire, it was found that adolescents who had a good level of knowledge during the pretest were 5 adolescents (18%) and increased to 23 adolescents (82%) during the posttest. With the increasing understanding of the concept of emotional mental disorders, forms of disorders, causative factors, and emotional mental measurements, it is hoped that adolescents will be able to apply the knowledge and abilities of adolescents to handle emotional mental health problems such as stress and anxiety that occur in everyday life.